THE ROLE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH TO MEDICAL STUDENTS: THE ROLE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH TO MEDICAL STUDENTS - Nurlibaeva, Nargiza (Журнал иностранных языков и лингвистики, 2025)
ronment, improving teamwork and patient outcomes [6]. In the contemporary era, which is characterized by the prevalence of global connections, the capacity to engage in cross-cultural interactions is becoming an increasingly crucial skill. [1; 214] Traditional methods of teaching English often fall short in addressing the unique linguistic needs of medical students [4; 139] This study examines the role of AI in bridging this gap. The application of AI in language learning can be supported by educational theories such as Constructivism, which emphasizes active learning and knowledge construction, and Connectivism, which focuses on learning in a technology-rich environment. These frameworks validate the use of AI tools that promote engagement and facilitate the acquisition of medical language skills.